Asosiasi Aktivitas Fisik dengan Sembelit pada Mahasiswa Sekolah Ilmu Kesehatan Makassar - Chitra Dewi; Wahyu Wahyu (J-KESMAS: Jurnal Kesehatan Masyarakat, 2021)
Constipation is considered trivial and rarely treated seriously. Moreover, it can lead to a negative impact on health. Based on the US Census Bureau database, the incidence of constipation worldwide and in Indonesia is quite high, with around 12% of the population worldwide experiencing constipation. This study aimed to recognize the association of physical activity with constipation. This was quantitative research with a cross-sectional study design in that number of sample was 204 respondents of 415 populations selected by stratified random sampling. The results revealed a p-value = 0.000 indicated that there was a relationship between physical activity with constipation. It concluded that physical activity is associated with constipation. It is encouraged to the community to maintain a healthy diet, including adequate intake of dietary fiber, and conduct routine activities.